THE EFFECT OF DEBT TO EQUITY RATIO AND NET PROFIT MARGIN TOWARD PROFIT CHANGE IN PT. UNIT TRACTORS, TBK - Muhamad Syahwildan (Journal of Research in Business, Economics, and Education, 2019)
This study aims to determine the effect of Debt to Equity Ratio and Net Profit Margin on profit changes at PT. United Tractors. Tbk. Both simultaneously and partially. The dependent variable used in this study is Debt to Equity Ratio and Net Profit Margin while the independent variable is profit change. The sample used is the period 2009-2016. Data were processed using SPSS multiple linear regression software. The results of this study indicate that Debt to Equity significantly influences changes in profit, Net Profit Margin significantly influences profit changes, Debt to Equity and Net Profit Margin together significantly influence profit changes.